Energy Subsidies, Public Investment and Endogenous Growth - Mundaca, Gabriela (Elsevier, 2018)
We consider impacts of fossil fuel subsidy reforms on economic growth, focusing mostly on the Middle East and North Africa (MENA) countries. The main empirical result is that a country that initially subsidizes its fossil fuels, and then eliminates or reduces these subsidies, will as a result experience higher economic GDP per capita growth, and higher levels of employment and labor force participation, especially among the young. These effects are strongest in countries whose fuel subsidies are high at the outset, such as in the MENA region. Our model predicts that a 20 US$ cents average increase in the gasoline and diesel prices per liter, through removal of subsidies, increase the GDP per capita growth rate by about 0.48% and 0.30%, respectively. In the MENA countries, governments’ savings from reduced subsidies seem to be earmarked mainly to health expenditures, education expenditures and public investment in infrastructure. These channels appear to be strong contributing factors to higher long-run growth when fuel subsidies are reduced.